High-temperature, polymer-graphite hybrid composites for bipolar plates: effect of processing conditions on electrical properties - Radhakrishnan, S.; Ramanujam, B. T. S.; Adhikari, Arindam; Sivaram, S. (Journal of Power Sources, 2007)
High-temperature thermoplastic-graphite composites are prepared using polyphenylene sulfide (PPS) and polyether sulfone (PES) containing natural graphite powder. All samples are prepared by high pressure compaction and heating to high temperatures. The effect of a third additional conducting component on the electrical resistance of these composites is studied. A low resistance of the order of 0.1 Omega can be obtained even for a graphite concentration of 50% by addition of the third component. The effect of a mixing/blending technique on the anisotropy of conductivity is investigated. Solution blending of PES with graphite leads to lower anisotropy values than powder mixing and compression moulding. The samples when exposed continuously to a working temperature of 100 degrees C give a small but significant reduction in electrical resistance. X-ray diffraction studies on composites prepared by different techniques indicate that there is restructuring and crystallite re-orientation of the graphite phase in the samples. A large reduction in the crystallite size is observed for samples prepared by solution blending while re-orientation occurs after heat treatment. The changes in electrical properties can be correlated with these structural transformations in the composites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bipolar plates; conducting polymer; fuel cell; graphite composites; hybrid materials; polyether sulfone; polypherylene sulfide

Polyethersulfone-expanded graphite nanocomposites: charge transport and impedance characteristics - Ramanujam, B. T. S.; Mahale, Rajashree Y.; Radhakrishnan, S. (Composites Science and Technology, 2010)
Polyethersulfone (PES)-expanded graphite nanocomposites have been prepared by solution blending route after sonicating expanded graphite in dichloromethane. It has been observed that ultrasonication results in nanosheets formation leading to a low percolation threshold of 3 wt.%. At 5 wt.% filler loading the conductivity is of the order of 10(-2) S/cm. Hopping type of charge transport occurs at 3.2 wt.% expanded graphite in PES below which capacitive effects couple. The effective dielectric constant at low frequency increases with filler concentration. Impedance measurement has been carried out to evaluate interfacial capacitance which, for 3.2 wt.% expanded graphite addition in PES, increases to 110 pF from 32 pF for 1 wt.% expanded graphite in the polymer. DSC analysis shows an increment of 12 C in the T(g) of PES with 3 wt.% expanded graphite suggesting interaction between the polymer and filler. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Electrical properties; Modeling; Polymers; Scanning/transmission electron microscopy (STEM)

Analysis of electrical and thermal conductivities of polyethersulfone-graphite based hybrid nanocomposites - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, Shripad D. (Macromolecular Research, 2017)
Polyethersulfone (PES)-7 wt% graphite- x wt% filler (carbon black (CB), carbon nanofiber (CNF), expanded graphite (ExGr)) hybrid composites are synthesized by solution blending route. The electrical percolation threshold in hybrid composites varies exponentially with the aspect ratio of the second conducting filler. The aspect ratio of the second conducting filler has been found to vary in the order CB < CNF < ExGr. The percolation threshold is identified at 0.05 wt%, 0.4 wt%, 1.3 wt% for ExGr, CNF and CB added PES-7 wt% graphite composites. Through plane thermal conductivity of PES-x wt% graphite-y wt% CB (x=10, 20, 30, 40, 50, 60, y=0, 3, 7) hybrid composites has been found to increase with the addition of CB. Thermal conductivity has been increased to 0.42 W/m-K when 7 wt% CB is added to PES-60 wt% graphite from 0.2 W/m-K. Reduction of interparticular distance with the increased loading of CB facilitates better thermal transport. Aspect ratios of second conducting fillers have been found out from transmission electron microscopy and scanning electron microscopy analysis.

Polyphenylene sulfide- expanded graphite nanocomposites: processing route dependent electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Polyphenylene sulfide (PPS)-expanded graphite (ExGr) conducting nanocomposites have been prepared by powder mixing and in situ polymerization routes after sonicating ExGr particles in acetone. Synthesized PPS has been used to make powder mixed composites. The powder mixed composites exhibit a percolation threshold of 3 wt% due to the formation of graphite nanosheets. When PPS-ExGr composites are prepared by in situ polymerization route, very low electrical percolation threshold less than 0.5 wt% ExGr is obtained. The low percolation threshold obtained is attributed to better dispersion of ExGr nanosheets in the polymer matrix when compared to powder mixed composites. The synthesized PPS has been characterized by X-ray diffraction, differential scanning calorimetry, and infrared spectroscopy. The formation of graphite nanosheets has been confirmed by transmission and scanning electron microcopy analysis.

Polypropylene-based conducting nanocomposites: effect of aspect ratio of second conducting filler on the electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Powder-mixed polypropylene (PP)-graphite binary composites exhibit an electrical percolation threshold at 10 wt% graphite signifying insulator-semiconductor transition. Three conducting fillers such as carbon black (CB), sonicated expanded graphite (s-ExGr), and carbon nanofiber (CNF) are mixed with PP-7 wt% graphite binary composites. The electrical percolation threshold has been found to have inverse relation to the aspect ratio of second conducting fillers in hybrid composites. The aspect ratio of second conducting fillers varies in the order CB < ExGr < CNF. The electrical percolation threshold is found to vary for the hybrid composites as 2.2 wt% for CB addition, 0.75 wt% for ExGr addition, and 0.2 wt% for CNF addition in the PP-7 wt% graphite binary composites. When the aspect ratio of second conducting fillers increases, they reduce the barrier for the charge transport. The second conducting fillers occupy the interspace of graphite and alternating current studies show that the effective dielectric constant increases with the concentration of second conducting filler in the hybrid composites. The composites are characterized by transmission electron microscopy and scanning electron microscopy. Melt-crystallized PP-7 wt% graphite-CNF composites exhibit higher percolation threshold due to decrease in the polymer viscosity which increases the interparticulate distance.
Keywords: carbon nanofiber; Conducting polymer composites; Electrical properties; graphite nanosheets; hybrid composites; percolation; scanning; transmission electron microscopy